Safety of Amlodipine in Early Pregnancy. Issue 15 (6th August 2019) - Mito, Asako; Murashima, Atsuko; Wada, Yoshinao; Miyasato‐Isoda, Mai; Kamiya, Chizuko A.; Waguri, Masako; Yoshimatsu, Jun; Yakuwa, Naho; Watanabe, Omi; Suzuki, Tomo; Arata, Naoko; Mikami, Masashi; et al.
Abstract : Background: Amlodipine is used for the treatment of hypertension, but reports on its use in early pregnancy are limited. Methods and Results: In the present study, we recruited 231 women with chronic hypertension, including those who received amlodipine or other antihypertensives during early pregnancy, and investigated frequencies of morphologic abnormalities in their 231 offspring. Specifically, we evaluated 48 neonates exposed to amlodipine in the first trimester (amlodipine group, Group A), 54 neonates exposed to antihypertensives other than amlodipine (other antihypertensive group, Group O), and 129 neonates not exposed to antihypertensives (no‐antihypertensive group, Group N). The number of morphologic abnormalities of offspring in each group were 2 in Group A (4.2%; 95% CI, 0.51–14.25); 3 in Group O (5.6%; 95% CI, 1.16–15.39) and 6 in Group N (4.7%; 95% CI, 1.73–9.85). The odds ratio of the primary outcome comparing Group A and Group O was 0.74 (95% CI: 0.118–4.621) and Group A and Group N was 0.89 (95% CI: 0.174–4.575). Conclusions: The odds of birth defects in Group A in the first trimester were not significantly different from those with or without other antihypertensives.